VD_FINDINFO Jug / 2024 / 347 vom 25. September 2023 - VD Tribunal cantonal (2023)
FAUX MATÉRIEL DANS LES TITRES, PEINE PÉCUNIAIRE, SURSIS À L'EXÉCUTION DE LA PEINE, AMENDE | 106 CP, 251 CP, 34 CP, 42 CP